Implementation of Lesson Study by Dominating Discovery Learning and TGT Models to Increase Student Learning Interest - Islamiyah, Aris Mislikhatun; Suparni, Suparni; Azka, Raekha; Hayati, Siti Rahmatun (JPMI (Jurnal Pendidikan Matematika Indonesia), 2025)
This study aims to improve students' interest in learning This study aims to increase students' interest in learning mathematics by implementing Lesson Study that combines Discovery Learning and Teams Games Tournament (TGT) models. The method used in this research is descriptive qualitative, which was conducted on students of class XE MAN 4 Sleman for the academic year 2024/2025. Data were obtained through questionnaires, observation, and documentation. The research was conducted in two cycles which included planning, implementation, and reflection stages. The results showed a significant increase in students' interest in learning. At the end of Cycle I, only 18.18% of students showed very high interest in learning, while at the end of Cycle II, the percentage increased to 51.51%. This increase shows the effectiveness of applying a combination of Discovery Learning and TGT models in increasing students' interest in learning mathematics. In Cycle I, various obstacles were still found, such as low student participation, teacher dominance in learning, and learning outcomes that had not reached the KKM target. Therefore, Cycle II planning focused on empowering student involvement through interesting and collaborative media. After making improvements in Cycle II, there was a significant increase in both student interest and involvement, as well as the achievement of the research success indicators. Thus, the research was stopped at Cycle II because the objectives had been achieved, and Lesson Study can be concluded as an effective strategy to increase students' interest in learning.Penerapan Lesson Study Dengan Mendominasi Model Discovery Learning Dan TGT Untuk Meningkatkan Minat Belajar SiswaABSTRAKPenelitian ini bertujuan untuk meningkatkan minat belajar matematika siswa dengan menerapkan Lesson Study yang menggabungkan model Discovery Learning dan Teams Games Tournament (TGT). Metode yang digunakan dalam penelitian ini adalah deskriptif kualitatif, yang dilaksanakan pada siswa kelas XE MAN 4 Sleman untuk tahun ajaran 2024/2025. Data diperoleh melalui angket, observasi, dan dokumentasi. Penelitian dilakukan dalam dua siklus yang mencakup tahap perencanaan, pelaksanaan, dan refleksi. Hasil penelitian menunjukkan peningkatan yang signifikan dalam minat belajar siswa. Pada akhir Siklus I, hanya 18,18% siswa yang menunjukkan minat belajar sangat tinggi, sedangkan pada akhir Siklus II, persentase tersebut meningkat menjadi 51,51%. Peningkatan ini menunjukkan efektivitas penerapan kombinasi model Discovery Learning dan TGT dalam meningkatkan minat siswa terhadap pembelajaran matematika. Pada Siklus I, masih ditemukan berbagai kendala, seperti rendahnya partisipasi siswa, dominasi guru dalam pembelajaran, serta hasil belajar yang belum mencapai target KKM. Oleh karena itu, perencanaan Siklus II difokuskan pada pemberdayaan keterlibatan siswa melalui media yang menarik dan kolaboratif. Setelah dilakukan perbaikan pada Siklus II, terjadi peningkatan yang signifikan baik dari segi minat maupun keterlibatan siswa, serta tercapainya indikator keberhasilan penelitian. Dengan demikian, penelitian dihentikan pada Siklus II karena tujuan telah tercapai, dan Lesson Study dapat disimpulkan sebagai strategi yang efektif untuk meningkatkan minat belajar siswa.Kata Kunci:Pendidikan; Lesson study; minat belajar